Implementation Manual: CCAFS Climate-Smart Monitoring Framework - Tackling uptake of CSA options and perceived outcomes at household and farm level - Bonilla Findji, Osana; Eitzinger, Anton; Andrieu, Nadine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
As part of the Learning Platform (LP2) Participatory evaluation of Climate-Smart Agricultural (CSA) practices and technologies across the AR4D Climate-Smart Villages (CSVs) network, CCAFS Flagship 2 designed a new Integrated Climate-Smart Monitoring Framework to supports a global, systemic and standardized effort to build context-specific evidence on uptake of CSA options and the associated (perceived) outcomes at household and farm level.